A Review of the Analytical Methods for the Determination of 4(5)-Methylimidazole in Food Matrices - Panagiota-Kyriaki Revelou (MDPI AG, 2021)
4(5)-Methylimidazole (4(5)MEI) is a product of the Maillard reaction between sugars and amino acids, which occurs during the thermal processing of foods. This compound is also found in foods with caramel colorants additives. Due to its prevalence in foods and beverages and its potent carcinogenicity, 4(5)MEI has received federal and state regulatory agency attention. The aim of this review is to present the extraction procedures of 4(5)MEI from food matrices and the analytical methods for its determination. Liquid and gas chromatography coupled with mass spectrometry are the techniques most commonly employed to detect 4(5)MEI in food matrices. However, the analysis of 4(5)MEI is challenging due to the high polarity, water solubility, and the absence of chromophores. To overcome this, specialized sample pretreatment and extraction methods have been developed, such as solid-phase extraction and derivatization procedures, increasing the cost and the preparation time of samples. Other analytical methods for the determination of 4(5)MEI, include capillary electrophoresis, paper spray mass spectrometry, micellar electrokinetic chromatography, high-performance cation exchange chromatography, fluorescence-based immunochromatographic assay, and a fluorescent probe.